Multilayered targets for superheavy element production - Cerboni Noemi; Stephens Kyle J.; Shepelin Nick A.; Müller Elisabeth A.; Steinegger Patrick; Maugeri Emilio A. (EPJ Web of Conferences)
The production of superheavy elements requires targets capable of withstanding prolonged, high-intensity heavy ion-beam bombardment. Current methods, such as molecular plating, produce actinoid films with insufficient stability under these conditions. To address this, a thermally superior solid solution between actinoids and Pd has been synthesized using the coupled reduction process and successfully tested. To further improve said technique, we aimed at confining Tb (i.e., a surrogate for late actinoid elements) within a thin Pd layer with a thickness of a typical target layer suitable for superheavy element synthesis. The thin Pd film was initially deposited onto a support composed of a Ni backing foil and a TiN layer intended to block the diffusion of Tb and Pd into the underlying Ni during coupled reduction. The thermal stability of the obtained multilayered samples and the diffusion behavior of Tb were studied by cross-sectional analysis via scanning electron microscopy coupled with focused ion beam milling and energy dispersive X-ray spectroscopy.